Portable Exoskeleton Glove With Soft Structure for Hand Assistance in Activities of Daily Living - Popov, Dmitry; Gaponov, Igor; Jee-Hwan Ryu (IEEE/ASME transactions on mechatronics, 2017)
This paper presents a new portable exoskeleton glove developed for assistance in activities of daily living (ADL). The proposed glove is soft, adjustable, allows unconstrained motion of the wrist, and leaves the palm free for object grasping and manipulation. In the proposed design, both flexion and extension motions of the thumb and three fingers (excluding the little finger) are supported by respective bidirectional actuators. The kinematics of the device were derived and are presented along with an experimental evaluation. The developed glove system is compact and light, with the weights of the wearable part and the whole system being 250 and 340 g, respectively. The maximum pinch force provided by the device was experimentally measured to be 16 N, which gives the proposed device one of the highest power-to-weight ratio among existing portable devices for hand ADL assistance. The usability of the developed device was verified in a series of indoor and outdoor tests. The glove allowed test subjects to hold and manipulate versatile objects with diameters up to 90 mm and weighing 300 g. When powered by a conventional 3000-mAh battery, the glove could operate continuously performing grasping task for 4 h.